Protaetia brevitarsis larvae extract ameliorated obesity in high fat diet-fed mice by modulating gut microbiota and lipid metabolism - Zongqi Zhang; Sicong Chen; Qinglei Wang; Chunqin Liu; Jinhua Xiao; Dawei Huang (Food Science and Human Wellness)
Due to the rapid development of obesity and related metabolic diseases in the world, it is particularly important to explore the ability of novel materials in regulating obesity. In this study, C57BL/6J obese mice were used as objects, and 16S rRNA gene sequencing and lipidomics techniques were used to explore the regulatory effect and mechanism of the Protaetia brevitarsis ethanol extract (50%, V/V) against obesity. Our results showed that P. brevitarsis extract could significantly reduce the body weight, triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and pro-inflammatory cytokines (tumor necrosis factor-α (TNF-α), interferon-γ (IFN-γ), and interleukin-6 (IL-6)) levels of high-fat diet (HFD)-fed mice. Moreover, the P. brevitarsis extract changed the composition and relative abundance of its gut microbiota, especially increasing Akkermansia muciniphila. Meanwhile, the content of short-chain fatty acids (SCFAs) was increased, especially acetic acid and butyric acid, which leads to a decrease in the synthesis and accumulation of lipids in the liver. Furthermore, the P. brevitarsis extract also induced the difference in lipid synthesis in the liver by down-regulating the mRNA levels of sterol regulatory element binding protein-1C (SREBP-1C), fatty acid synthase (FAS), and acetyl-CoA carboxylase (ACC). Therefore, this research provided preliminary work and reference for the development of P. brevitarsis as a functional food for anti-obesity.